2000
DOI: 10.1038/sj.ijo.0801127
|View full text |Cite
|
Sign up to set email alerts
|

No effect of gender on different components of daily energy expenditure in free living prepubertal children

Abstract: BACKGROUND: There are limited and controversial data on the in¯uence of gender on metabolic rate in prepubertal children. OBJECTIVE: To assess the effect of gender on resting energy expenditure (REE), activity-related energy expenditure (AEE), total energy expenditure (TEE) and physical activity level (PAL) in free-living prepubertal children. DESIGN: Cross-sectional study. SUBJECTS: 40 prepubertal children (24 boys, 16 girls, 4 ± 11 y old (mean age: 7.0 AE 1.2 y), BMI 13.1 ± 32.0 kgam 2 ). MEASUREMENTS: Energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 23 publications
2
16
1
Order By: Relevance
“…This fact suggests that the previously reported higher REE in adult men cannot be explained entirely by differences in sex hormones. Contrary to previous studies but in a reduced group of prepubertal children (24 boys and 16 girls), GRUND et al (14) have shown that gender had no significant effect on REE. Our results show that gender determines REE strongly in non-obese group but it has no influence on obese group.…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…This fact suggests that the previously reported higher REE in adult men cannot be explained entirely by differences in sex hormones. Contrary to previous studies but in a reduced group of prepubertal children (24 boys and 16 girls), GRUND et al (14) have shown that gender had no significant effect on REE. Our results show that gender determines REE strongly in non-obese group but it has no influence on obese group.…”
Section: Discussioncontrasting
confidence: 45%
“…More prospective studies are necessary to determine the effect of body composition factors on REE variability over time and its impact on obesity development. Biochem., 58 (1), [9][10][11][12][13][14][15][16]2002.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Basement recruitment included (i) assessment of the nutritional state by anthropometric methods as well as bioelectrical impedance measurements; 17 (ii) dietary assessment by a standardised food frequency questionnaire; 18 (iii) assessment of physical activity and social state by different questionnaires, 19 -21 risk factors (blood pressure, blood glucose, cholesterol, triglycerides by standard procedures) and resting as well as 24 h energy expenditure, physical activity, muscle strength and physical fitness in a subgroup of children. 22,23 Representativity of the cohorts was tested and assured by comparing sociodemographic as well as nutritional data (body weight, height, BMI) with the total group of 5 to 7-y-old children born in 1989 in Germany and investigated by the school physicians in Schleswig Holstein. 24 This group consisted of 25 338 5 to 7-y-old children (12 289 girls, 13 049 boys) which were 92.6% of all children born in Schleswig Holstein, the capital of Schleswig Holstein, in 1989.…”
Section: Study Participiantsmentioning
confidence: 99%
“…Individually FLEX-HR was used to discriminate between resting and exercise HR. Total energy expenditure was measured by the FLEX-HR monitoring method as described previously 40,41 . For the remainder of the daytime, when HR was above FLEX-HR, energy expenditure was derived from the minute-by-minute recorded HR using the individual child's regression line for the VO 2 corresponding to HR 15 .…”
Section: Hr Monitoringmentioning
confidence: 99%